PERANCANGAN SISTEM INFORMASI PELAYANAN PURNA JUAL BERBASIS CUSTOMER RELATIONSHIP MANAGEMENT - Andy Dharmalau; Yogasetya Suhanda; Lela Nurlaela (Institut Teknologi dan Bisnis (ITB) Swadharma, 2021)
Information is an important factor, which is very influential in realizing a dynamic business world and fast growing. Today's business world is developing along with technological advances, both in the service and non-service sectors. The Jakarta motor repair shop is a company engaged in motor vehicle repair services. The Jakarta motorbike repair shop is experiencing various problems in its operations, namely the slow processing of transaction data, reports and the absence of communication with customers to remind the routine maintenance of the vehicle. To solve existing problems and fulfill management's wishes, then an application that combines the concept of information systems is designed communication using short message service (SMS). This application system runs well, overcoming problems in workshop operations.can send vehicle routine maintenance schedule information to customers, expected to increase customer loyalty.